Impact of Water Meter Replacement on a Water Utility’s Revenue - Brinkley, Meghan (My University, 2019)
Water demand management focuses on implementing a number of smaller projects which have the potential to reduce water usage. Focus has been placed on meter replacement projects, based on the premise that water meter accuracy degrades over time. Johannesburg Water embarked on a water meter replacement project, with a focus on replacing water meters which had not been read due to technical faults. By making use of the meter reading information provided by Johannesburg Water, for the old meter and new meter, a comparison of a year’s worth of consumption was undertaken. Further the effect of the meter size, chronological age and volumetric age was considered. The average monthly revenue increase was calculated for the entire sample (3679 properties). This translated to an average monthly revenue increase per-property-per-month of approximately R304. Results indicate that there is no one-size-fits all meter replacement strategy, Water Utilities need to consider their unique conditions.
A Research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. April 2019
Keywords: Water-meters--South Africa; Municipal water supply--South Africa--Costs